2019
DOI: 10.3390/cancers11020209
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Treatment Suppresses Melanoma Cell Growth and Motility Through Modulation of microRNA Expression

Abstract: Melanoma is a highly aggressive cancer with high mortality in advanced stages.Metformin is an oral biguanide drug used for diabetes and has demonstrated positive effects oncancer prevention and treatment. Herein, we found that metformin significantly suppressedmelanoma cancer cell motility and growth through inducing cell cycle arrest at the G2/M phase andpromoting cell apoptosis. Using the next-generation sequencing approach, we identified threeupregulated microRNAs (miRNA; miR-192-5p, miR-584-3p, and miR-124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 65 publications
8
51
1
Order By: Relevance
“…Briefly, 350-µL serum samples were prepared following the manufacturer's protocol and using the NEBNext small RNA library prep kit (Cat#E7300, New England Biolabs, Ipswich, MA, USA). The detailed process for preparing serum samples was described in our previous study 29 . Afterwards, with the Illumina MiSeq platform, the small RNA libraries were sequenced (150 cycle, single read; MiSeq Reagent kit V3_150 cycles; Illumina, San Diego, CA, USA).…”
Section: Measures Of Symptomatologymentioning
confidence: 99%
“…Briefly, 350-µL serum samples were prepared following the manufacturer's protocol and using the NEBNext small RNA library prep kit (Cat#E7300, New England Biolabs, Ipswich, MA, USA). The detailed process for preparing serum samples was described in our previous study 29 . Afterwards, with the Illumina MiSeq platform, the small RNA libraries were sequenced (150 cycle, single read; MiSeq Reagent kit V3_150 cycles; Illumina, San Diego, CA, USA).…”
Section: Measures Of Symptomatologymentioning
confidence: 99%
“…Inhibition of the mTOR/S6/4EBP1 axis is known to impair protein synthesis and cell proliferation [53]. Metformin is also shown to exert regulative functions on miRNAs [6], which results in growth inhibition and cell viability impairment. In addition, metformin has been reported to inhibit epithelial-to-mesenchymal transition (EMT) to suppress tumor progression [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the concentration of metformin had an important effect on its action [43]. The concentration used in this study was based on the previous research [6].…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations